Prenatal diagnosis and follow‐up of a case of branchio‐oto‐renal syndrome displays renal growth impairment after the second trimester. Issue 11 (30th July 2015) - Bertucci, Emma; Mazza, Vincenzo; Lugli, Licia; Ferrari, Fabrizio; Stanghellini, Ilaria; Percesepe, Antonio
Abstract: Branchio‐oto‐renal syndrome combines branchial arch defects, hearing impairment and renal malformations or hypoplasia. Due to the high phenotypic variability, prenatal diagnosis has a limited prognostic value in mutation‐positive cases. We report the first branchio‐oto‐renal syndrome molecular prenatal diagnosis and ultrasonographic follow‐up, showing a normal renal growth until the 24th week of pregnancy, a growth deceleration during the third trimester and a renal volume recovery during the first months of life.